Direitos cívicos e políticos na infância e adolescência: da retórica da participação ao protagonismo infantil - Barbosa, Inês (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2020)
In this article we reflect on the 30 years of civil and political rights, legitimized by the Convention on the Rights of the Child. After a brief history and framing of these rights, we analyze concepts, practices and arenas of participation, paving the way for the defense of an approach for “child protagonism”. In this sense, the analysis highlights the constraints and possibilities of initiatives to promote participation. We ended with a reflection on the new challenges facing child and youth citizenship, launching some clues for debate.